2022
DOI: 10.1111/maps.13812
|View full text |Cite
|
Sign up to set email alerts
|

Formation of chondrule fine‐grained rims from local nebular reservoirs

Abstract: Chondrules are commonly surrounded by fine‐grained rims (FGRs) whose origin remains highly debated; both nebular and parent body settings are generally proposed. Deciphering their origin, however, is of fundamental importance as they could clarify the matrix–chondrule relationship and thus constrain the formation and transport conditions of chondrules in the circumsolar disk. Here, we report a systematic survey of FGRs in CO, CM, CV, and CR chondrites; we compare (i) the thickness of FGRs to the size of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 75 publications
2
14
0
Order By: Relevance
“…For instance, some chondrules in the Paris CM chondrite extend for more than 400 μm (Zanetta et al 2021). Likewise, type I rimmed chondrules in CR Renazzo and CV Vigarano exhibit elongated edges of about 400 μm (Pinto et al 2022).…”
Section: Numerical Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, some chondrules in the Paris CM chondrite extend for more than 400 μm (Zanetta et al 2021). Likewise, type I rimmed chondrules in CR Renazzo and CV Vigarano exhibit elongated edges of about 400 μm (Pinto et al 2022).…”
Section: Numerical Setupmentioning
confidence: 99%
“…The depth of embayments in rimmed chondrules found in chondrites varies considerably. While two rimmed chondrules in the CO chondrite DOM 08006 (Zanetta et al 2022, Figure 1) and one chondrule in CO EM 397 (Pinto et al 2022, Figure 1) show at most relatively shallow indentations (∼10 μm), a chondrule in CR QUE 99177 (Zanetta et al 2022, Figure 1) and two chondrules in CV Vigarano (Pinto et al 2022, Figure 1) exhibit larger depressions (∼100 μm). This range of embayment depths can also be observed within CM Paris alone (Zanetta et al 2021, Figure 1).…”
Section: Fgr Morphology and Impact Speedsmentioning
confidence: 99%
“…Still, even if the parental cloud was originally homogeneous, one would expect larger grains (i.e., those with longer stopping times) to settle first, which could explain the positive correlation between chondrule size and metamorphic subtypes in CO chondrites (e.g., Pinto et al, 2021). Similarly, submicrometer-sized matrix monomers accreted last as dark inclusions or fine-grained rims around chondrules (e.g., Metzler et al, 1992;Pinto et al, 2022;Zanetta et al, 2021), which was confirmed by the lack of correlation between the matrix fraction in CO chondrites and their petrologic subtypes (McSween, 1977). Although McSween (1979) reported an ~20 vol% increase in matrix fraction from the least to the most altered CMs, the modal matrix abundances in the recently described weakly altered CMs are similar to those in common CMs (Hewins et al, 2014;Kimura et al, 2020;Marrocchi et al, 2014).…”
Section: Implications For the Variable Formation Conditions Of Cr Cho...mentioning
confidence: 99%
“…This interpretation is consistent with multiple melting events of chondrules (e.g., Rubin & Wasson 1987;Wasson 1993;Baecker et al 2017). However, this does not provide the explanation for the larger thicknesses of igneous rims compared to fine-grained rims (Matsumoto et al 2021), the isotopic relations between igneous rims and their host chondrules (Jacquet et al 2015), or the association between igneous rims and fine-grained rims (Pinto et al 2022). Additional mechanisms would work to form igneous rims, such as the accretion of droplets (Jacquet et al 2013(Jacquet et al , 2015.…”
Section: Introductionmentioning
confidence: 97%